Analisis Penentuan Jenis Melon Terbaik Menggunakan Metode AHP pada Jagasura Farm Tegal - Shandy Ariffatulloh; Sri Lestari (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2026)
Selecting melon varieties that align with consumer preferences is essential for enhancing customer satisfaction and supporting purchasing decisions in the agribusiness sector. However, melon selection is often conducted subjectively because it involves multiple quality attributes, including sweetness, texture, appearance, size, and aroma. This study aims to identify the most preferred melon variety based on consumer preferences using the Analytical Hierarchy Process (AHP). The research was conducted at Jagasura Farm, Tegal, involving 30 consumers to assess the importance of selection criteria and three farm managers as experts to evaluate alternative melon varieties. Data were analyzed through pairwise comparisons, geometric mean calculations, matrix normalization, and consistency testing. The results indicate that sweetness was the most influential criterion with a priority weight of 0.355, followed by texture (0.204), appearance (0.187), size (0.172), and aroma (0.082). The ranking results show that Lavender melon achieved the highest global synthesis weight (0.303), followed by Sweet Net (0.281), Sweet Hami (0.233), and Inthanon (0.182). A Consistency Ratio (CR) of 0.033 confirms the reliability and consistency of the evaluations. These findings demonstrate that AHP is an effective decision-support method for selecting melon varieties based on consumer preferences.